Effects of standardized acoustic stimulation in premature infants: a randomized controlled trial - Wirth, Lara; Lemmer, Björn; Gorbey, Stefan (Journal of perinatology, 2016)
Objective: The objective of this study was to investigate the effects of recorded lullabies and taped maternal voice in premature infants. Study design: Sixty-two preterm infants in a stable condition with 30<37 weeks of gestation and <10 days of postnatal age were randomly assigned to hear (A) recorded lullabies or (B) taped maternal voice for 30 min each evening during 14 consecutive days or (C) receive no standardized acoustic stimulation (control group). Heart rate and respiratory rate were recorded daily before, during and after the intervention (A and B) or a comparable period with no intervention (C), whereas activity was measured on days 1, 7 and 14 of the intervention using accelerometers. Results: Both interventions led to a significant decrease in heart rate and respiratory rate during and after the stimulation when compared with the control group. The changes were more pronounced in infants with higher gestational ages (P=0.001). Lower activity was measured during the intervention when compared with the control group (P<0.01). Conclusions: Standardized acoustic stimulation with recorded lullabies and taped maternal voice led to a decrease in heart rate and respiratory rate, and was associated with lower activity. Whether this indicates a reduced stress reaction needs to be investigated in further studies.
Gesehen am 01.07.2019